METAL TRANSPORT ACROSS HUMAN CELL MEMBRANES - Omar S. Hajjawi (European Scientific Journal, ESJ, 2014)
The field of ‘inorganic biochemistry’ is rapidly changing due to metal ions properties which are rendered indispensable in cellular biochemistry. At least, twenty six of the hundred eighteen periodic table elements are now known to be involved in the biochemistry of the human body. Their various physical properties are utilized in a subtle and sometimes unexpected ways to serve biochemical purpose. The essential trace elements or inorganic micronutrients invariably have a catalytic function, and are found in the metabolic pathways controlling other substrates assimilation and utilization in the synthesis of new cells and in the use of cell energy. Many studies have exposed that the imbalance of zinc, iron, and copper which are cofactors of many enzymes, can affect various cancers and diseases like Alzheimer’s, Parkinson’s and hypertension. The pathogenesis of essential hypertension is associated with increased exchangers activity of Na+/Li+, Na+/H+ and Na+/K+ ATPase. Therefore, it is crucial to develop an inclusive understanding how regulating metal levels in human body is of importance to eliminate any significant effects of various toxic metals on human health. The syndromes of pneumoconiosis, neuropathies and hepatorenal degeneration develop slowly over time and it may be difficult to diagnose chronic exposure to metal dusts. Therefore, this review is restricted to the normal biological activities of metals, though the gross physiological effects of metal deficiency or toxicity will not be ignored.